Development of East coast economic corridor and Vizag-Chennai Industrial Corridor. - Banerjee, Pritam (South Asia working papers., 2017)
This paper provides a detailed discussion of the policies and strategies that should be considered to attain the overall objective of improving shipping and air connectivity in ECEC and VCIC while developing an enabling environment for efficient logistics support businesses that play a critical role in the management of global supply chains. The ECEC and VCIC will align with the national objectives of expanding domestic markets, pursuing port-led industrialization, and integrating domestic companies into the vibrant global value chains of Southeast Asia and East Asia.